Isolation, BODIPY Labeling and Uptake of Exosomes in Hepatic Stellate Cells - Shubham Shrivastava (Bio-Protocol, 2017)
Exosomes have emerged as an important mediator of intercellular communication. They are present in extracellular milieu and therefore, easily accessible by neighboring or distant cells. They carry mRNA, microRNAs and proteins within their vesicles and once internalized by recipient cells; they can modulate multiple signaling pathways with pleiotropic effects from inducing antiviral state to disease progression. We have previously shown that hepatitis C virus (HCV) infected hepatocytes or hepatoma cells harboring genome-length replicon secrete exosomes in culture supernatants. These exosomes are taken up by hepatic stellate cells (HSC) and activate them to induce fibrosis during HCV infection. Here, we describe detailed protocols for exosomes isolation and uptake of BODIPY labeled exosomes by hepatic stellate cells.